GnRHa implants and temperature modulate Lambari-do-rabo-amarelo, Astyanax altiparanae (Characiformes: Characidae) induced reproduction out of the reproductive season - Brambila-Souza, Gabriela [UNESP]; Mylonas, Constantinos Chrysanthos; de Mello, Paulo Henrique [UNESP]; Kuradomi, Rafael Yutaka; Batlouni, Sergio Ricardo [UNESP]; Tolussi, Carlos Eduardo; Moreira, Renata Guimarães (Hindawi, 2021)
We evaluated the effect of gonadotropin in controlled-release implant together with temperature manipulation in the reproduction of Astyanax altiparanae (lambari) during the non-breeding season. Three groups of adult females were maintained at 20°C and three at 28°C. For each temperature, one group was treated with 4 μg GnRHa g−1, other with 8 μg GnRHa g−1 and other was sham implanted as a control during 4 weeks. Afterwards, 4 females/experimental group were induced to spawn with human chorionic gonadotropin, while 4 females/group were injected with saline. GnRHa implants increased fshβ and lhβ gene expression in females maintained at 28°C. The vtgA gene expression increased in the high GnRHa dose at 20°C, while this higher GnRHa dose associated with the higher temperature increased Gonadosomatic Index. The hCG injection increased the plasma Mature Induction Steroid levels and trigger ovulation, except in control at 28°C. The control females at 20°C spawned but with low reproductive performance, confirming that this is not a limiting temperature for reproduction. The administration of GnRHa as implant increased gonadotropin gene expression at 28°C, temperature at which GSI also increased. Qualitatively, the implants improved reproduction at 20°C, providing offspring out of the reproductive season, improving lambari production throughout the year.
Keywords: gonadotropins; neotropical fish; ovaries; steroids; vitellogenin